Corrosion resistance of passive films on different stainless steel grades in food and beverage industry. (15th August 2020) - Santamaria, M.; Tranchida, G.; Di Franco, F.
Highlights: Stainless steel samples were passivated in food and beverage industry environments. Passive films were characterized by Photocurrent Spectroscopy and EIS measurements. Dissolution kinetic of metal and passive film has been studied by ICP–OES tests. Abstract: Passive films were grown on 304 L, 316 L and Duplex stainless steels by immersion at open circuit potential in solutions mimicking food and beverage industry environments. In acidic food stainless steel surfaces are covered by Cr rich passive films, and generalized dissolution occurs on their surface with consequent ions release into the electrolyte. In fatty food the concentration of released ions is significantly lower since generalized corrosion does not occur, but the loss on MnS inclusions strongly reduces the polarization resistance in this environment especially for 304 L due to its higher localized corrosion susceptibility with respect to the other grades.